A Mixed Method Research on Peer Assessment - Gokhan Izgar; Ahmet Oguz Akturk (International Journal of Evaluation and Research in Education (IJERE), 2018)
The purpose of this study is to investigate the relationship between peer assessment and instructor assessment and make a comparison with views of preservice teachers. Since qualitative and quantitative methods were used together in the study, it was grounded on the mixed method approach. The quantitative data in this study, in which 27 preservice teachers participated on a voluntary basis, were obtained from scoring rubric whereas qualitative data were obtained from a semi-structured interview form prepared by the researchers. Statistical analyses were conducted to analyze the quantitative data collected within the scope of the study, whereas Pearson Product-Moment Correlation Coefficient was used to analyze the relationship between instructor assessment and peer assessment, and paired samples t test was used to determine the differences between pairwise groups. The qualitative data, on the other hand, were analyzed using the content analysis technique. As a result of the analysis, it was seen that there was a positive and significant correlation between instructor assessment and peer assessment. When the preservice teachers’ views were examined, those views rose to prominence stating that making assessments contributed to learning; they grew aware of imperfect knowledge; questioning and critical thinking improved, and fair assessment skills developed. This was interpreted to mean that preservice teachers could distinguish between adequate and inadequate work. However, when the preservice teachers’ views concerning their assessments by their peers were examined, the view attracted attention stating that friendship relations and personal problems affected assessment negatively and therefore peers gave low scores. At this point, when the mean scores were examined, it was seen that mean peer scores were higher than instructor mean scores. This was interpreted to mean that some preservice teachers did not have confidence in their peers.